FRI0308 Predictors of hypogammaglobulinaemia in rituximab treated patients. a retrospective analysis on a monocentric cohort. (15th June 2017) - Padoan, R; Felicetti, M; Gatto, M; Polito, P; Ometto, F; Astorri, D; Friso, L; Cozzi, F; Doria, A; Punzi, L; Schiavon, F
Abstract : Background: Rituximab (RTX), a chimeric monoclonal antibody against CD20, is increasingly used in the treatment of B-cell lymphomas and autoimmune conditions. It has been shown that some patients develop hypogammaglobulinaemia after treatment. Objectives: To assess frequency and predictors of hypogammaglobulinaemia after RTX treatment in a monocentric cohort of patients affected with granulomatosis with polyangiitis (GPA), microscopic polyangiits (MPA) and connective tissue diseases (CTD). Methods: We retrospectively reviewed all patients receiving RTX and concomitant/sequential immunosuppressants between 2007 and 2016 in a single rheumatologic center. Serum levels of total Ig and lymphocyte subsets were recorded at the time of RTX administration and 3–6 months later. We investigated the frequency of hypogammaglobulinaemia (IgG<6 g/L) and its related events. Results: 72 patients, 30 (41.6%) GPA/MPA, 25 (34.7%) systemic lupus erythematosus, 13 (18.1%) systemic sclerosis and 4 (5.6%) poly-dermatomyositis were treated with RTX. We analyzed 113 RTX infusions, with 41 (36.2%) retreatments (median 2 [2–6]). We excluded 12 patients/18 infusions due to incomplete data. RTX was administered at the dosage of 1000 mg twice in 68.1% of patients and 375 mg/m 2 weekly in 31.9%. IgG levels after RTX infusion were available in 68 (71.6%) patients. We observed a significant decrease of IgG levels between baseline and 3–6 months after RTX infusion in all patients (0.001). The frequency of patients with IgG<6 g/L was 22.1%, and 8.8% had IgG<4 g/L, significantly higher in GPA/MPA patients (0.008), with short disease duration (0.001), lower IgG levels at baseline (0.008), higher prednisone equivalent (PDE) cumulative dosage per year (0.006) and higher daily PDE dosage after RTX (0.001) (Table 1). After RTX, all patients had complete B-cells depletion. At univariate analysis, IgG<6 g/L was associated with GPA/MPA diagnosis (0.006, OR 6 [1.5–24.2]), disease duration (<0.001, OR 0.2 [0.1–0.9]), RTX 375 mg/m 2 weekly protocol (p=0.017, OR 4.1 [1.2–13.9]), PDE cumulative dosage per year (<0.001, OR 6.6 [1.3–33.6]), daily PDE intake >15 mg/day after RTX (<0.001, OR 12.7 [3.1–52.5]) and IgG levels before RTX (<0.001, OR 18 [1.8–178]). At multivariate analysis, daily PDE intake after RTX (>15 mg/day) and GPA/MPA diagnosis resulted independent predictive factors for hypogammaglobulinaemia (p=0.03, OR 9.5, [2.2–41.7] and p=0.43, OR 4.7, [1.1–21.5]). Patients affected with GPA/MPA were compared to CTD, as reported in Table 2. GPA/MPA patients at infusion were older (0.002), presented shorter disease duration (0.001), lower IgG levels at baseline (<0.001) despite lower rate of nephrotic syndrome (0.003). Moreover they were treated more frequently with Azathioprine (0.007), RTX 375 mg/m 2 weekly protocol (<0.001) and higher PDE cumulative and daily dosage (<0.001, 0.01 respectively). Only 5 patients (5.2%) experienced severe infections within 12 months, more frequently in IgG<6 g/L patients (0.007). Conclusions: In autoimmune rheumatic diseases, diagnosis of GPA/MPA and glucocorticoid therapy resulted independent predictors of hypogammagobulinaemia after RTX treatment. Despite low IgG levels were associated with higher infections risk, rare severe infectious events were observed. Disclosure of Interest: None declared